Perceived effect of sport participation on menstrual cycle among female athletes in Yenagoa, Bayelsa State, Nigeria - Kpai, Tonubari; Abel, Favour Brother (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2023)
The global shift in societal and cultural attitudes towards the inclusion of female athletes in the sporting arena has contributed to a surge in the participation of women in competitive sports in recent years. The menstrual cycle and other female-specific physiological traits may be negatively impacted by these activities. This study investigated the perceived effect of sports participation on the menstrual cycle among female athletes in the Yenagoa local government area of Bayelsa State, Nigeria. The descriptive survey design was adopted. A stratified sampling technique and snowballing technique were used to select 160 respondents from the study area. A structured questionnaire with a reliability coefficient of 0.834 was used to collect data, retrieval rate was 93.8%. Data was subjected to descriptive and inferential statistical analysis. Findings from the study revealed the female athletes had a mean menarche age of 13.25±1.68 years, a mean menstrual cycle duration of 28.30±4.15 days, and a mean menstrual flow of 4.30±0.84 days. The majority of the respondents (27.8%) who experienced very severe menstrual pain were found among respondents with very active sports participation. Findings further revealed that sports participation had no significant effect on age at menarche (F= 1.447, p= 0.239), duration of the menstrual cycle (F= 2.170, p= 0.118), and length of menstrual flow (F= 0.516, p= 0.598) but had a significant effect on menstrual pain (F= 5.056, p= 0.002). Thus, coaches and personal trainers should regularly organise workshops/training for female athletes on the management and balancing of sporting activities about their menstrual cycle; in addition, female athletes should maximise each phase of their cycle for optimum participation and performance.